2023
DOI: 10.1590/0103-8478cr20210467
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modification influences the mechanical resistance of wood from forestry species

Abstract: This study evaluated the effects of thermal modification at different temperatures and for different durations on the mechanical strength of wood of selected species from an agroforestry system. To this end, three 9-year-old (approximate age) individuals, each from four species of forest trees-Parapiptadenia rigida (Benth.) Brenan, Peltophorum dubium (Spreng.) Taub., Eucalyptus grandis × Eucalyptus urophylla hybrid, and Schizolobium parahyba (Vell.) Blake-were evaluated. After obtaining initial measurements, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…To evaluate the influence of one parameter on another in the correlation analysis, as in the case of the anatomical and physical properties of wood, it is essential that the species studied show heterogeneity among themselves. This is an important characteristic, because heterogeneous materials are mandatory to more accurately evaluate the influence of anatomical parameters on the physical properties of wood (Eloy et al, 2023). This is justified by the fact that the different species studied have different anatomical parameters and, consequently, their physical properties differ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate the influence of one parameter on another in the correlation analysis, as in the case of the anatomical and physical properties of wood, it is essential that the species studied show heterogeneity among themselves. This is an important characteristic, because heterogeneous materials are mandatory to more accurately evaluate the influence of anatomical parameters on the physical properties of wood (Eloy et al, 2023). This is justified by the fact that the different species studied have different anatomical parameters and, consequently, their physical properties differ.…”
Section: Discussionmentioning
confidence: 99%
“…When we analyze the dimensions of the fibers, we can infer that the highest CWF values found for the species P. rigida, P. dubium and E. grandis × E. urophylla are associated with the basic density, since they are directly proportional (Table 4). This relationship results in the highest values for this physical property, as well as for all other mechanical properties, making the material more resistant (Eloy et al, 2023). On the other hand, lower CWF values result in a lower basic density of the wood (Lima et al, 2014), corroborating the results found for S. parahyba, which were lower average CWF values (21.6%) (Table 2) and, consequently, lower basic density values (0.277 g cm -3 ) (Table 3).…”
Section: Between Vf and Woodmentioning
confidence: 96%
See 2 more Smart Citations